2016
DOI: 10.1158/0008-5472.can-15-2092
|View full text |Cite|
|
Sign up to set email alerts
|

Aberrant Notch Signaling in the Bone Marrow Microenvironment of Acute Lymphoid Leukemia Suppresses Osteoblast-Mediated Support of Hematopoietic Niche Function

Abstract: More than half of T-ALL patients harbor gain-of-function mutations in the intracellular domain of Notch1. Diffuse infiltration of the bone marrow commonly occurs in T-ALL and relapsed B-ALL patients, and is associated with worse prognosis. However, the mechanism of leukemia outgrowth in the marrow and the resulting biological impact on hematopoiesis are poorly understood. Here, we investigated targetable cellular and molecular abnormalities in leukemia marrow stroma responsible for the suppression of normal he… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 49 publications
5
44
0
Order By: Relevance
“…The use of conditioned medium prepared from ex vivo cultures of N1ICD-transplanted bone marrow was sufficient to reproduce the process, arguing that tumor cells may act through secreting soluble factors [71]. Recently, with the use of the same model of Notch-dependent T-ALL, Wang and collaborators [72] reported that N1ICD leukemic cells in the bone marrow microenvironment induced both the suppression of the endosteal/osteoblast niche and the alteration of the perivascular region, thus impairing proliferation and homing of HSC progenitors. Besides, the authors described a progressive expansion of Gr1 + myeloid cells in a nontransformed compartment, mainly influenced by tumor cells, through an induced activation of Notch signaling in the bone marrow stroma.…”
Section: The ''Nononcogenic'' Consequences Of An Oncogene: Suppress Tmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of conditioned medium prepared from ex vivo cultures of N1ICD-transplanted bone marrow was sufficient to reproduce the process, arguing that tumor cells may act through secreting soluble factors [71]. Recently, with the use of the same model of Notch-dependent T-ALL, Wang and collaborators [72] reported that N1ICD leukemic cells in the bone marrow microenvironment induced both the suppression of the endosteal/osteoblast niche and the alteration of the perivascular region, thus impairing proliferation and homing of HSC progenitors. Besides, the authors described a progressive expansion of Gr1 + myeloid cells in a nontransformed compartment, mainly influenced by tumor cells, through an induced activation of Notch signaling in the bone marrow stroma.…”
Section: The ''Nononcogenic'' Consequences Of An Oncogene: Suppress Tmentioning
confidence: 99%
“…Besides, the authors described a progressive expansion of Gr1 + myeloid cells in a nontransformed compartment, mainly influenced by tumor cells, through an induced activation of Notch signaling in the bone marrow stroma. This led to the up-regulated expression of inflammatory cytokines, such as IL-6 [72]. IL-6 represents one of the most important factors determining expansion and activation of MDSCs, following the so-called "2-signal" theory of their differentiation [73].…”
Section: The ''Nononcogenic'' Consequences Of An Oncogene: Suppress Tmentioning
confidence: 99%
“…Moreover, treatment of AML mice with compounds that inhibit osteoblast loss increased survival (14). In T-cell acute lymphoblastic leukemia (T-ALL) Notch overexpression suppressed osteoblast differentiation (16). In contrast, in a myeloproliferative neoplasia (MPN) mouse model an increase in trabecular number and thickness was observed and functional osteoblast were replaced by altered osteoblast that overproduced pro-inflammatory cytokines and myeloid differentiation signals (17).…”
Section: Commentarymentioning
confidence: 99%
“…Using four-dimensional imaging, Hawkins et al pointed out how T-ALL cells invade the bone marrow and lead to rapid remodeling of the endosteal niche, with a total loss of mature osteoblasts. Similarly, using a mouse model of Notch-driven T-ALL, Wang et al [32] showed that leukemic cells affect the homing of healthy HSCs, compete for the occupancy of perivascular areas and suppress the number of osteoblasts, disrupting the normal hematopoiesis. The authors demonstrated the key role of Notch pathway in these processes, since Notch blockade recovered the osteoblasts and fostered HSCs proliferation in vivo.…”
Section: Leukemia March To the Marrow: A New Landlordmentioning
confidence: 99%